1976
DOI: 10.1111/j.1432-1033.1976.tb10855.x
|View full text |Cite
|
Sign up to set email alerts
|

Active Transport by Membrane Vesicles from Anaerobically Grown Escherichia coli Energized by Electron Transfer to Ferricyanide and Chlorate

Abstract: Active transport of amino acids by membrane vesicles from Eschrricizicr cnli, grown anaerobically on glucose in the presence of nitrate, can be energized under anaerobic conditions by electron transfer in the nitrate respiration system with formate as electron donor and nitrate as acceptor. A high rate of amino acid transport is also obtained under anaerobic conditions by electron transfer from formate to the nitrate analogue chlorate or to the membrane-impermeable electron acceptor ferricyanide. Electron tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…Ferricyanide can accept electrons from electron transport chains in membrane vessicles of B. subtilis (32) and E. coli (39). It is possible that the Fe(III)-quinate that was used in the proton translocation studies can interact with electron transport components in a similar manner.…”
Section: Membrane-bound Fe(iii) Reductases Which Could Reducementioning
confidence: 99%
“…Ferricyanide can accept electrons from electron transport chains in membrane vessicles of B. subtilis (32) and E. coli (39). It is possible that the Fe(III)-quinate that was used in the proton translocation studies can interact with electron transport components in a similar manner.…”
Section: Membrane-bound Fe(iii) Reductases Which Could Reducementioning
confidence: 99%
“…Membrane vesicles prepared from anaerobically grown E. coli concentrate L-glutamate 230-fold under anaerobic conditions in the presence of formate as electron donor and nitrate as acceptor (Fig.4A) [22] and 500-fold under aerobic conditions with axorbate/ phenazine methosulphate (Fig. 4B).…”
Section: Involvement Of the Electrochemical Proton Gradient In The Enmentioning
confidence: 99%
“…It has been shown previously that electron transfer in the nitrate respiration system supplies the energy for active t I'LL nsport of amino acids under anaerobic conditions [7.17-191. Experiments performed with spheroplasts by Garland et al [20, 211 and studies in membrane vesicles [22] with the membrane-impermeable electron acceptor ferricyanide suggested that components of the nitrate respiration system are exposed to different sides of the membrane. These observations and the demonstration that nitrate respiration results in the translocation of protons across the membrane [20] and in the generation of a A$ [7,22] indicated that an electrochemical proton gradient might be the driving force for active transport under anaerobic conditions.…”
mentioning
confidence: 99%
“…Ferricyanide can accept electrons from electron transport chains in membrane vessicles of B. subtilis (32) and E. coli (39). It (11).…”
Section: Enumeration and Culturing Of Fe(hi) And Mn(iv) Reducersmentioning
confidence: 99%